K problematice současného úzu paroxytonického přízvuku v mluvě západních a jižních Čech - Holub, Zbyněk (Slavia Centralis, 2020)
The occurrence of the accent on the penult in contemporary western and southern Bohemia In this paper the author focuses on the peculiarities of stress (referred to as "accent on the penultima") in southern and western Bohemia, a phenomenon he has documented in 70–80% of relevant syllables in southern and western Bohemia, north and west of Pilsen. The stress on the first syllable is typically more consistent at the beginning of the disyllabic word which forms a stress-prosodic domain with a previous syllable or with an unstressed proclitic, as evidenced in the Doudleby region, in the Manětín region, and south of Pilsen.